2019
DOI: 10.3390/ijms20020395
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Liver Axis, Gut Microbiota, and Its Modulation in the Management of Liver Diseases: A Review of the Literature

Abstract: The rapid scientific interest in gut microbiota (GM) has coincided with a global increase in the prevalence of infectious and non-infectivous liver diseases. GM, which is also called “the new virtual metabolic organ”, makes axis with a number of extraintestinal organs, such as kidneys, brain, cardiovascular, and the bone system. The gut-liver axis has attracted greater attention in recent years. GM communication is bi-directional and involves endocrine and immunological mechanisms. In this way, gut-dysbiosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
276
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(347 citation statements)
references
References 100 publications
8
276
0
11
Order By: Relevance
“…135,136 Peripheral Vd2 T cells are depleted in obese individuals (in a BMIdependent manner), 137,138 are more likely to exhibit a T EMRA phenotype and respond poorly to influenza-infected APCs, 138 mirroring the effects of HIV infection, HBV/HCV infection and renal disease on this compartment. 139,145,146 Finally, obese individuals also exhibit elevated levels of LPS and other markers of microbial translocation, supporting a putative link between gut permeability, low-grade inflammation, and cd Tcell depletion and dysfunction. 138 Interestingly, these three conditions, as well as HIV infection, all involve some degree of gut dysbiosis.…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…135,136 Peripheral Vd2 T cells are depleted in obese individuals (in a BMIdependent manner), 137,138 are more likely to exhibit a T EMRA phenotype and respond poorly to influenza-infected APCs, 138 mirroring the effects of HIV infection, HBV/HCV infection and renal disease on this compartment. 139,145,146 Finally, obese individuals also exhibit elevated levels of LPS and other markers of microbial translocation, supporting a putative link between gut permeability, low-grade inflammation, and cd Tcell depletion and dysfunction. 138 Interestingly, these three conditions, as well as HIV infection, all involve some degree of gut dysbiosis.…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 87%
“…125 Similar observations have been made in the context of chronic HCV/HBV infection and liver cirrhosis, where overgrowth of pathogenic gut bacteria increases gut permeability and allows translocation of bacterial products into the liver via the portal vein. 139,145,146 Finally, obese individuals also exhibit elevated levels of LPS and other markers of microbial translocation, supporting a putative link between gut permeability, low-grade inflammation, and cd Tcell depletion and dysfunction. 147,148…”
Section: Similarities With Other Chronic Inflammatory Diseasesmentioning
confidence: 87%
“…The lower proportions of unconjugated bile acids (Figure C) and secondary bile acids (Figure D) seen in our study are consistent with previous reports, , which suggest an altered gut microbiome in patients with NASH. Additionally, an increased Firmicutes/Bacteroidetes ratio has been reported in patients with NAFLD, NASH and diabetes . Because deconjugation of glycine and taurine is caused by many bacteria including Bacteroides , Clostridium , Lactobacillus, Bifidobacterium, Eubacterium , Peptostreptococcus and Streptococcus , it is possible that total bacterial numbers in the gut microbiome are decreased in NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also confirmed that there are various links between the gut and the liver, and that gut microbiota are also involved in intestinal metabolism through the microbiota-gut-liver axis [31,32]. Therefore, this article mainly summarizes the role of the gut microbiota in neuroendocrine regulation of carbohydrates, lipids, and amino acids via the microbiota-gut-brain-liver axis.…”
mentioning
confidence: 96%
“…The bidirectional communication that occurs for the microbiota-gut-brain axis includes "bottom-up" (from gut microbiota to brain) and "top-down" (from brain to gut microbiota) [29,30]. For example, gut microbiota can regulate levels of gut peptides to influence the vagal afferent pathway and regulate intestinal metabolism via the microbiota-gut-brain axis [23][24][25].Several studies have also confirmed that there are various links between the gut and the liver, and that gut microbiota are also involved in intestinal metabolism through the microbiota-gut-liver axis [31,32]. Therefore, this article mainly summarizes the role of the gut microbiota in neuroendocrine regulation of carbohydrates, lipids, and amino acids via the microbiota-gut-brain-liver axis.…”
mentioning
confidence: 99%